The Impact of Entomological Sample Handling Techniques on a Single Larva Odor Profile - Ana Zoe Monogan; Joshua L. Smith; Paola A. Prada-Tiedemann (Forensic Sciences, 2025)
Background: Chemical odor profiling within forensic entomology is an emerging tool given its potential for species identification and larval aging and its ability to identify decomposition stages. A volatile analysis of larval masses across species of distinctive developmental stages was carried out with extraction techniques to identify odor signatures. However, it is unknown how larval sample handling (i.e., live samples in research vs. hot-water-killed samples in casework) affects odor signatures or the possibility of obtaining relevant volatiles from a single larva. Method: This study utilized solid-phase microextraction (SPME) with gas chromatography–mass spectrometry (GC/MS) for the analysis of odor volatiles emanating from single larval samples of Cochliomyia macellaria. Fifty (50) larvae (25 live; 25 boiled) were analyzed. Results: The SPME-GC/MS method allowed for odor volatile detection from a single maggot regardless of the sample handling group. The main compounds identified across both groups included those previously reported as emanating from larvae and decomposition substrates. When comparing treatments, the boiled larval samples had a 6-fold decrease in compound abundance compared to the live samples. The identified odor volatiles observed in the hot-water-killed treatment group included indole, p-cresol, and phenol. Conclusions: These results suggest that the handling technique impacts odor detection. Additionally, the heterocyclic aromatics and alcohols identified in the boiled samples are potentially odor markers of a higher intrinsic nature to the maggot rather than a cross-transfer from the decomposition substrate given their survival post elevated temperature treatment. This work shows the plausibility of carrying out an odor analysis of a single maggot following both common research and casework handling practices.